The Implementation of Strategic Management by Madrasah Principals in Improving Teacher Performance at Annuriyah Bontocini Tsanawiyah Madrasah, Jeneponto District - Nur Alam Saputra; Umar Sulaiman; Alwan Subhan (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This research aims to analyze the planning and implementation of the Strategic Management of the Madrasah Principal in improving teacher performance at Madrasah Tsanawiyah Annuriyah Bontocini, Jeneponto Regency. The research findings indicate that the madrasah principal has successfully implemented strategic management principles regularly and gradually. This process involves three main stages: strategy formulation (internal-external analysis and setting measurable targets), strategy implementation (through comprehensive programs such as training, workshops, academic supervision, and work ethic development), and strategy evaluation and control (periodic monitoring). The implementation of this strategic management proved to bring positive and significant changes to teacher performance. The improvement in teacher performance is notably seen in pedagogical and professional competence, work discipline, initiative, and commitment. Teachers feel more directed and motivated, supported by open communication and clear work direction from the madrasah principal acting as a strategic leader. The madrasah principal plays an important role in aligning all resources with the madrasah's vision and mission and creating a positive work culture. Nevertheless, there are some constraints, such as limited budget, resources, execution time, and variations in individual teacher readiness/motivation.